Mapping of biogas production potential from livestock manures and slaughterhouse waste: A case study for African countries. (20th May 2020) - Ali, Mohamed Mahmoud; Ndongo, Mamoudou; Bilal, Boudy; Yetilmezsoy, Kaan; Youm, Issakha; Bahramian, Majid
Abstract: Despite the remarkable potential for biogas production from livestock and organic wastes, the number of constructed biogas digesters for the continent is in the order of thousands and in case of Mauritania is lower than the number of the provinces. While majority of the existing digesters left far behind the expected efficiency, lack of a comprehensive economic assessment along with an efficient design questions their practical application. The present study introduced the first assessment to evaluate the biogas potential from livestock manures and waste from slaughterhouses in Northwest Africa (a case of Mauritania). Using ArcGIS® software, a database was conducted to build maps that show the amount of waste products, the potential of biogas, and equivalent amounts of energy. These were used to assess the potential of biogas and the corresponding potential energy for each geographical department in Mauritania. The results indicated that the southern provinces had the highest biogas potential with the maximum and the average values of 520 and 258.7 (±125.8) × 10 6  m 3 /year. On the other hand, the lowest biogas production potential (27.7 × 10 6  m 3 /year) was recorded for northern provinces with the maximum and the average values of 135 and 76.4 (±39.7) × 10 6  m 3 /year. The results showed that 63, 579 × 10 6  kg of waste associated with livestock (cattle) and slaughterhouse applications were annually produced in the country. It was determined that this quantity could generate 2451 × 10 6  m 3 of biogas per year, corresponding to an energy potential of 52, 704 × 10 6  MJ/year. Considering the rapid depletion of conventional energy sources and the significance of biogas as a renewable fuel, a detailed feasibility analysis (for the biogas production in each province of Mauritania by means of community type fixed-dome digesters) was also performed in the scope of this study. The results of the comprehensive cost breakdown analysis revealed that the revenues obtained from sale of biogas-generated electricity and digested slurry (as fertilizer) could able to pay the initial investment within approximately 6.5 years without subsidy. The findings of this study, as the first of its own, could be used to comprehend how utilization of information such as slaughterhouse and livestock population, nutrition habitats, land-usage maps and geographic information system (GIS) can be employed to germinate a model for more comprehensive assessment of biogas production potential from livestock manure and slaughterhouse wastes, specifically in case of northern African countries. Moreover, in case of biogas plant, this model could be employed as a decision-making tool to identify the highly qualified location for construction of the biogas plant. Highlights: Mapping of biogas production potential is conducted in Mauritania for the first time. 63, 579 × 10 6  kg of waste can generate 2451 × 10 6  m 3 of biogas per year in the country. The southern provinces are found to have approximately 4 times more biogas potential. Energy production in Mauritania heavily depends on oil, natural gas, and wood fuels. A nationwide biogas digester project can pay for itself in 6.5 years without subsidy.